The role of hair loss in cancer identity: perceptions of chemotherapy-induced alopecia among women treated for early-stage breast cancer or ductal carcinoma in situ - Trusson, Diane; Pilnick, Alison (2016)
Background: The trauma of chemotherapy-induced alopecia is well documented. However, less is known about how the stereotypical cancer identity affects social interactions.